2005
DOI: 10.1007/s10439-005-3555-3
|View full text |Cite
|
Sign up to set email alerts
|

Osteoblast Elastic Modulus Measured by Atomic Force Microscopy Is Substrate Dependent

Abstract: The actin and microtubule cytoskeleton have been found to contribute to the elastic modulus of cells, which may be modulated by adhesion to extracellular matrix (ECM) proteins and subsequent alterations in the cytoskeleton. In this study, the apparent elastic modulus (Eapp) of osteoblast-like MC3T3-E1 cells adhered to fibronectin (FN), vitronectin (VN), type I collagen (COLI), fetal bovine serum (FBS), or poly-l-lysine (PLL), and bare glass were determined using an atomic force microscope (AFM). The E(app) of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
104
1
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(124 citation statements)
references
References 73 publications
17
104
1
2
Order By: Relevance
“…AFM studies revealed cell stiffnesses between ,0.1 and 0.6 kPa for untreated cells, which is similar to elastic moduli described for other osteoblast-like cell lines (Domke et al, 2000;Takai et al, 2005). After adrenergic stimulation with clenbuterol the osteoblast-like CAL-72 cells appeared much stiffer.…”
Section: Discussionsupporting
confidence: 79%
“…AFM studies revealed cell stiffnesses between ,0.1 and 0.6 kPa for untreated cells, which is similar to elastic moduli described for other osteoblast-like cell lines (Domke et al, 2000;Takai et al, 2005). After adrenergic stimulation with clenbuterol the osteoblast-like CAL-72 cells appeared much stiffer.…”
Section: Discussionsupporting
confidence: 79%
“…This result is in line with previous reports (64)(65)(66)(67)(68). Moreover, this result is consistent with that obtained by SICM based on the proposed model that the elasticity of the cells in the control group is higher than those treated with CD and Noc, and that the elasticity of the cells with CD is even smaller than those with Noc (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…These include, among others, cardiocytes [33], osteoblasts [12,13,91], glia [29,100], fibroblasts [28,46,98], erythrocytes [8,20] (review), oocytes [103], and outer-hair cells of Corti's organ, [67,89,90,95,96].…”
Section: Eukaryotesmentioning
confidence: 99%